Salicylic acid derivatives as potential anti asthmatic agents using disease responsive drug delivery system for prophylactic therapy of allergic asthma. (February 2016) - Rama Satyanarayana Raju, Kalidhindi; Ambhore, Nilesh S.; Mulukutla, Shashank; Gupta, Saurabh; Murthy, Vishakantha; Kiran Kumar, M.N.; Madhunapantula, Subba Rao V.; Kuppuswamy, Gowthamarajan; Elango, Kannan
Abstract: Asthma is a multi-factorial and complicated lung disorder of the immune system which has expanded to a wider ambit unveiling its etiology to be omnipresent at both ends of the spectrum involving basic pharmacology and in-depth immunology. As asthma occurs through triggered activation of various immune cells due to different stimuli, it poses a great challenge to uncover specific targets for therapeutic interventions. Recent pharmacotherapeutic approaches for asthma have been focused on molecular targeting of transcription factors and their signaling pathways; mainly nucleus factor kappa B (NFκB) and its associated pathways which orchestrate the synthesis of pro-inflammatory cytokines (IL-1β, TNF-α, GM-CSF), chemokines (RANTES, MIP-1a, eotaxin), adhesion molecules (ICAM-1, VCAM-1) and inflammatory enzymes (cyclooxygenase-2 and iNOS). 5-aminosalicylic acid (5-ASA) and sodium salicylate are known to suppress NFκB activation by inhibiting inhibitor of kappa B kinase (IKκB). In order to target the transcription factor, a suitable carrier system for delivering the drug to the intracellular space is essential. 5-ASA and sodium salicylate loaded liposomes incorporated into PEG-4-acrylate and CCRGGC microgels (a polymer formed by crosslinking of trypsin sensitive peptide and PEG-4-acrylate) could probably suit the needs for developing a disease responsive drug delivery system which will serve as a prophylactic therapy for asthmatic patients.